Temporal associations between low body condition, lameness and milk yield in a UK dairy herd - Green, L.E.; Huxley, J.N.; Banks, C.; Green, Martin J. (Elsevier, 2014)
Previous work has hypothesised that cows in low body condition become lame. We tested this in a prospective longitudinal study. Body condition score (BCS), causes of lameness and milk yield were collected from a 600-cow herd over 44-months. Mixed effect binomial models and a continuous outcome model were used to investigate the associations between lameness, BCS and milk yield. In total, 14,320 risk periods were obtained from 1137 cows. There were 1510 lameness treatments: the most common causes of lameness were sole ulcer (SU) (39%), sole haemorrhage (SH) (13%), digital dermatitis (DD) (10%) and white line disease (WLD) (8%). These varied by year and year quarter. Body condition was scored at 60-day intervals. BCS ranged from 1 to 5 with a mean of 2.5, scores were higher in very early lactation but varied widely throughout lactation; approximately 45% of scores were <2.5. The key finding was that BCS < 2.5 was associated with an increased risk of treatment for lameness in the following 0–2 months and >2–4 months for all causes of lameness and also specifically for SU/WLD lameness. BCS < 2.5 was associated with an increased risk of treatment for SH in the following 0–2 months but not >2–4 months. There was no such association with DD. All lameness, SU/WLD, SH and DD were significantly more likely to occur in cows that had been lame previously, but the effect of BCS was present even when all repeat cases of lameness were excluded from the analysis. Milk yield was significantly higher and fell in the month before treatment in cows lame with SU/WLD but it was not significantly higher for cows that were treated for DD compared with non-lame cows. These findings support the hypothesis that low BCS contributes to the development of horn related claw lameness but not infectious claw diseases in dairy cows. One link between low BCS and lameness is a thin digital cushion which has been proposed as a trigger for claw horn disease. Cows with BCS 2 produced more milk than cows with BCS 2.5, however, this was only approximately 100 kg difference in yield over a 305-day lactation. Given the increased risk of lameness in cows with BCS 2, the direct costs of lameness and the small variability in milk yield by BCS, preventing cows from falling to BCS < 2.5 would improve cow welfare and be economically beneficial.